Characteristics and phylogenetic analysis of the complete chloroplast genome of Gardneria multiflora Makino 1901 from the family Loganiaceae - Guangyan Li; Bing Li; Guosi Li; Xiangwen Song (Mitochondrial DNA. Part B. Resources)
Gardneria multiflora Makino is an important medicinal plant endemic to China, with its roots and leaves traditionally used for therapeutic purposes. In this study, we report the complete chloroplast genome of G. multiflora. The 144,920 bp genome (GC 37.82%) has a typical circular quadripartite structure: 98,036 bp LSC, 18,382 bp SSC, and two 14,251 bp IRs. It has 125 unique genes, comprising 82 protein-coding, 35 tRNA, and 8 rRNA genes. Phylogenetic analysis revealed that G. multiflora is closely related to G. ovata. The data presented in this study can guide future research on the evolutionary history of this species.